Assessment of Learner Outcomes As a Model for Evaluation of Distance Education - Joan Laughlin (Journal of Applied Communications, 1998)
The graduate faculty of the College of Human Resources and Family Sciences, University of Nebraska, distance deliver a Master of Science degree. Twenty-four graduates participated in the Assessment of Student Outcomes (89% participation rate) wherein students rated their self-efficacy (Bandura, 1986) in meeting course objectives. The goal was that 80% of graduates would rate the master’s program as adequately preparing them for their post-master’s professional role; and they would rate themselves as being able to locate, analyze and use resources, to interpret data in research reports and to use these research findings in professional roles. All 12 courses reached this goal, except for selected objectives for courses in statistics, research methods, and consumer economics. Self-analysis of attainment of learner objectives should be a helpful application for others conducting program assessment.